Corneal angiogenesis based on different protocols of alkaline cauterization in murine models - Claros-Chacaltana,Flor Diana Yokoay (2017)
Abstract Purpose: To establish and compare protocols of alkaline cauterization for inducing corneal angiogenesis in murine models. Methods: Twenty-four adult Wistar rats were distributed into four groups (G1, G2, G3, and G4). The right eye cornea from each rat was cauterized using filter paper (3 mm), soaked in a solution of silver and potassium nitrates (3:1). Cauterization times were 10 (G1 and G4), or 20 seconds (G2 and G3). Cauterized corneas were washed with Ringer’s lactate solution. The filter paper was either removed before washing (G1 and G2), or kept on the corneas (G3 and G4). Corneas were photographed at multiple time points (2, 4, 6, 8, 11, 13, and 15 days after the procedure), and neovascularization parameters were assayed. Results: Neovascularization was observed in 66% of G1 corneas, and 100% of G2, G3, and G4 corneas. On day 15, G1 corneas showed smaller vascularized areas (12.63 ± 12.59%) compared to those in the G3 (41.95 ± 17.32%) and G4 (33 ± 11.74%) (P < 0.05) groups. Conclusions: The silver and potassium nitrate solution effectively induced corneal angiogenesis. The G2, G3, and G4 protocols showed excellent reproducibility, and induced vascularization in 100% of corneas.